Language, the soul of the nation - Abd Razak, Dzulkifli (2006)
This Merdeka, we should appreciate the role the Malay language played in achieving independence. This week we celebrate the 49th year of Merdeka. We have not done too badly, compared with many countries that gained their independence about the same time. With the launching of the Third Industrial Master Plan (IMP3) recently, the country has taken another step in the right direction to become a developed nation. Universities and research institutes will be enhanced to ensure industrial growth contributes towards equitable distribution and balanced regional development. In short, development of human capital remains essential. The need is for the technically skilled in critical areas of science and engineering.